PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN JOB RELEVANT INFORMATION (JRI) DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Survei Pada Perusahaan Perbankan di Kota Jambi) - Primadi Prasetio; Junaidi; Asep Machpuddin (Magister Ilmu Akuntansi Universitas Jambi, 2016)
ABSTRACT For reaching the target for the increase of managerial performance to consider factors that can influence the issue, among others, the participation of the budget. Participation budget can not walk alone in influencing managerial performance, but there are other factors that synergize, including organizational commitment and job relevant information (JRI). Researchs on the factors that influence managerial performance such as participation of the budget, organizational commitment and job relevant information has been carried out by some studies, but most of the empirical evidence is varied and inconsistent, which concluded that there was no direct relationship modest between participation and performance, including in the banking industry where the variable budget participation and managerial performance is the deciding factor thrive whether or not these companies so that from this article, researchers interested in conducting a study entitled